Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/5423413
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antenatal Care Attendance among Pregnant Women Living in Endemic Malaria Settings: Experience from the Democratic Republic of Congo

Abstract: Background. Antenatal care (ANC) attendance helps pregnant women to benefit from preventive and curative services. Methods. Determinants for ANC attendance were identified through a cross-sectional survey in the Democratic Republic of Congo. Sociocultural bottlenecks were assessed via focus groups discussion of married men and women. Results. In this survey, 28 of the 500 interviewed pregnant women (5.6%) did not attend ANC services and 82.4% booked over the first trimester. The first visit is positively influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 12 publications
7
24
3
Order By: Relevance
“…According to [ 20 ], trends in most sub-Saharan countries seem to suggest that most women do not have their first ANC visit during the first trimester. In the current study however, 41.2% of the mothers had their first ANC visit in the first trimester which was about twice that reported (20.5%) from Cameroon [ 20 ] and a much higher level reported (82.4%) from the Democratic Republic of Congo [ 21 ]. Thus, some improvement is being seen in Africa at the start of implementation of the new WHO policy.…”
Section: Discussioncontrasting
confidence: 60%
“…According to [ 20 ], trends in most sub-Saharan countries seem to suggest that most women do not have their first ANC visit during the first trimester. In the current study however, 41.2% of the mothers had their first ANC visit in the first trimester which was about twice that reported (20.5%) from Cameroon [ 20 ] and a much higher level reported (82.4%) from the Democratic Republic of Congo [ 21 ]. Thus, some improvement is being seen in Africa at the start of implementation of the new WHO policy.…”
Section: Discussioncontrasting
confidence: 60%
“…Our study attempted to use 24 hours DDS which is a proxy measure of nutrition and whether it can correlate with MUAC in pregnant women attending the rst antenatal visit among women. The majority of the women booking in the second trimester is similar to a study conducted by Nsibu and others in the Democratic Republic of Congo where the majority of antenatal women reported to the clinic after the rst trimester (31). Reporting to the antenatal clinic in the rst trimester is important as ailments can be detected in good time and treated before affecting the foetus (32) .…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that less privileged women are less likely to access ANC services. 25 Secondly, the cross-sectional design cannot establish any causal relationship between anemia and the studied factors (ID and other associated factors). Finally, we did not investigate other possible causes of anemia such as hemoglobinopathies, genetic abnormalities, and the presence of helminths.…”
Section: Discussionmentioning
confidence: 99%